Green one-pot four-component synthesis of 3, 5-disubstituted isoxazoles- sulfonates and sulfonamides using a combination of NaDCC as metal-free catalyst and ultrasonic activation in water. (28th September 2021) - Talha, Aicha; Tachallait, Hamza; Benhida, Rachid; Bougrin, Khalid
Graphical abstract: Highlights: A simple and green one-pot four-component tandem reaction under ultrasound irradiation. Synthesis of novel 3, 5-disubstituted sulfonate and sulfonamide-isoxazoles in water. Sodium dichloroisocyanurate (NaDCC) as a base and water-soluble chlorinating agent. Experimental protocol using a safe, metal-free and eco-friendly reagents. Abstract: A simple and green one-pot reaction has been proposed for the synthesis of novel 3, 5-disubstituted isoxazole-sulfonates and -sulfonamides (5a-j ) in water under ultrasound irradiation. The methodology is based on the use of safe and environmentally friendly reagents and allows, via in-situ 1, 3-dipolar cycloaddition, an easy access to functionalized heterocycles with the creation of four new bonds (SO, CN, CO and CC). Comparison studies using classical magnetic stirring and ultrasound irradiation clearly showed that sonication promoted clean transformation, high yields (72–89%) and faster reactions (20–28 min). All the synthesized compounds were fully characterized by MS-ES, 1 H NMR, 13 C NMR spectroscopy and HPLC analysis.